2015
DOI: 10.1002/jmv.24267
|View full text |Cite
|
Sign up to set email alerts
|

Acute meningoencephalitis associated with echovirus 9 infection in Sri Lanka, 2009

Abstract: The aetiology of acute meningoencephalitis in Sri Lankan children and adults is poorly understood. This study was carried out to determine pathogens responsible for meningoencephalitis in Sri Lanka. A hospital-based cross-sectional study was performed using cerebrospinal fluid samples (22 adult and 17 pediatric) collected from August to December 2009 from patients clinically diagnosed with acute meningoencephalitis at two tertiary care hospitals in Sri Lanka. Routine microbiology for bacterial pathogens togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
1
12
1
Order By: Relevance
“…All study patients with available sequence data from the enterovirus 5 0 -NTR had infections with human Enterovirus B. Members of the Enterovirus B species have been widely identified as the most common cause of aseptic meningitis worldwide (Danthanarayana et al, 2015;Dos Santos et al, 2006;Wieczorek et al, 2016), and cause aseptic meningitis significantly more often than other enterovirus species (Lo et al, 2010). Echovirus 30 predominated in this cohort, especially during the years 2013 and 2014.Thisisinagreementwiththedatareportedbyotherswhofound a peak of enteroviral meningitis due to echovirus 30 in 2013 and 2014 in Central Europe (Rudolph et al, 2017;Wieczorek et al, 2016).…”
Section: Discussionsupporting
confidence: 69%
“…All study patients with available sequence data from the enterovirus 5 0 -NTR had infections with human Enterovirus B. Members of the Enterovirus B species have been widely identified as the most common cause of aseptic meningitis worldwide (Danthanarayana et al, 2015;Dos Santos et al, 2006;Wieczorek et al, 2016), and cause aseptic meningitis significantly more often than other enterovirus species (Lo et al, 2010). Echovirus 30 predominated in this cohort, especially during the years 2013 and 2014.Thisisinagreementwiththedatareportedbyotherswhofound a peak of enteroviral meningitis due to echovirus 30 in 2013 and 2014 in Central Europe (Rudolph et al, 2017;Wieczorek et al, 2016).…”
Section: Discussionsupporting
confidence: 69%
“…However, it also carries the risks of overlooking many potentially treatable diagnoses, and a high cost of unnecessary treatment. Interestingly, no cases of microbiologically confirmed HSV encephalitis were found in our study and in the two subsequent Sri Lankan studies described 52,53 . Intravenous acyclovir is widely used on an empiric basis in patients with suspected meningo-encephalitis in Sri Lanka, as was seen in our studies, and these findings challenge the rationale for this practice.…”
Section: Journal Of the Ceylon College Of Physicianscontrasting
confidence: 78%
“…Two Sri Lankan studies, conducted subsequent to our studies, have confirmed the difficulties in diagnosis in spite of access to good microbiological facilities. In a study by Danthanarayana et al (2015), Enterovirus (E-9) was detected in nine out of 39 CSF samples, and the samples were negative for all other viruses tested and bacterial culture 52 . Lohitharahjah et al (2017) identified a viral aetiology in 27.3% of 99 CSF samples from 108 patients with suspected encephalitis/ meningo-encephalitis; the aetiologies identified included dengue virus, JE virus, varicella zoster virus and West Nile virus.…”
Section: Study 1 Study 2 Study 2 Extension (Cnth Analysis) (Analysis mentioning
confidence: 98%
See 1 more Smart Citation
“…In previous studies, many serotypes of EV were reported of causing encephalitis outbreak in children, such as Echovirus 30 in Belgium, 2000, [20] Echovirus 6 in Greece, 2006, [21] Echovirus 4 in Spain, 2008, [22] Echovirus 19 in Uttar Pradesh, India, 2008, [23] Echovirus 9 in Sri Lanka, 2009, [24] and Coxsackievirus B5 in Henan, China [25] ; Echovirus 30 is a mostly common serotype in meningitis outbreaks caused by EV around the world. [26] According to the sequence of VP1 or 5 0 UTR, Echovirus 30 was found to be the major serotype in Hangzhou, 2015.…”
Section: Eve (Average)mentioning
confidence: 99%